The Association between Diurnal Sleep Patterns and Emotions in Infants and Toddlers Attending Nursery - Bacaro, Valeria (Brain Sci, 2020)
Background: Childcare programs often include mandatory naptime during the day. Loss of daytime sleep could lead to a moderate-to-large decrease in self-regulation, emotion processing, and learning in early childhood. Nevertheless, daytime sleep has been less accurately studied than nighttime sleep. This study aims to explore the relationship between diurnal sleep habits in nursery settings, nocturnal sleep quality, and post-nap emotional intensity in infants and toddlers. Methods: Data of 92 children (52 girls, 40 boys) aged 6 to 36 months were obtained. Sleep habits as well as positive and negative emotions were monitored by educators during nursery times through a sleep and emotion diary for two weeks. Results: Explorative analyses showed that diurnal sleep hours decreased across age groups (except for females aged 25–36 months) and that all age groups had a lower amount of nocturnal sleep than is recommended by the National Sleep Foundation. Partial correlation analysis showed significant correlation between daytime sleep onset latency and positive emotions. Mediation analyses showed that daytime napping is relevant for emotional functioning independently of nocturnal sleep quality. Conclusions: Daytime sleep in early childhood seems to be linked to the management of positive and negative emotions and could play a role in healthy development of emotional processes.